Manajemen Operasi Program Khutbah Jum’at Di Masjid Al Akbar Surabaya - Hari Santoso Wibowo; shokiful aziz; Bambang Subandi (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2019)
ABSTRACTThe function of the mosque in the history of its emergence is indeed not merely for "the place of prostration" as it literally means, but it has many functions. The mosque has another main function which is as a place of worship in preaching the values of Islam in people's lives. One form of syi'ar that can be performed in a mosque is the Friday Prayer. The purpose of this research is to describe the production management process of the Friday sermon program and the object of the Al Akbar National Mosque in Surabaya. This research uses a qualitative method with a Case Study approach. This study uses data collection techniques through interviews, observation and documentation. The data obtained came from the Chairman of Takmir / Managing Director, Head of Da'wah Division and several parties expected to be related to the program. Implementation of production management in the preparation of the Friday sermon program through several stages including the search for ideas through internal deliberations of the directorate of Imarah and the field of Da'wah, Selection of the preacher through qualification standards, Khatib Testing and Evaluation, the design of the sermon, the final design of the sermon.ABSTRAKFungsi masjid dalam sejarah kemunculannya, memang tidak sekedar untuk “tempat sujud” sebagaimana makna harfiahnya, tetapi memiliki banyak fungsi. masjid memiliki fungsi utama lainnya yaitu sebagai tempat syiar dalam mendakwahkan nilai – nilai Islam dalam kehidupan masyarakat. Salah satu bentuk syi’ar yang bisa dilaksanakan di masjid adalah shalat Jum’at. Tujuan dari penelitian ini ialah untuk menggambarkan proses manajemen produksi program khutbah Jum’at dan yang menjadi objeknya Masjid Nasional Al Akbar Surabaya. Penelitian ini menggunakan metode kualitatif dengan pendekatan Studi Kasus. Penelitian ini menggunakan teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Data yang diperoleh berasal dari Ketua Takmir/Direktur Utama, Kepala Bidang Dakwah  dan beberapa pihak yang diperkirakan terkait dengan program tersebut. Implemantasi manajemen produksi pada penyusunan progam khutbah jumat melalui beberapa tahapan diantaranya pencarian gagasan melalui musyawarah internal direktorat Imarah dan bidang Dakwah, Seleksi Khatib melalui standar kualifikasi, Pengujian dan Evaluasi Khatib, Desain khutbah, Desain akhir khutbah.